Performance improvement of aqueous zinc-iron flow batteries through organic ligand complexation of Fe(II)/Fe(III). (10th September 2020) - Kim, Yongbeom; Yun, Deokhee; Jeon, Joonhyeon
Abstract: In aqueous iron-based redox flow batteries (RFBs), there occurs a fatal performance degradation due to the formation of ferrihydrite via Fe(III) hydrolysis during long-term cycling. This paper describes an organic-ligand complexation of Fe(II)/Fe(III), which allows a high stability and reversibility of the Fe(II)/Fe(III) redox couple in aqueous zinc-iron RFBs. The remarkable effectiveness of pyridine chosen as a best complexing ligand is compared to seven organic ligands through various experiments including cell-cycling tests. It is experimentally confirmed that the pyridine initially coordinated to a Fe(II) cation forms a much strong bonding despite pH < 2, which leads to best electrochemical performances containing improved reaction kinetics and electron transfer. It also exhibits a slight discharge-capacity loss of only 2.9 % vs. 1 st cycle at 100 th cycle as compared to the pristine with an enormous loss of 78.7 % due to ferrihydrite precipitation, resulting in dynamically improved current efficiency with 73.34 % higher than the pristine one. Consequently, these results indicate that the pyridine as a complexing ligand agent can not only inhibit ferrihydrite during long-term cycling, but also enhance electrochemical stability and reversibility of the Fe(II)/Fe(III) redox couple. Graphical abstract: Image 1 Highlights: Fe(II) & Fe(III) complexation with pyridine is described for aqueous zinc-iron RFBs. Pyridine forms strongest bond to Fe(II)/Fe(III) as compared to seven organic ligands. Charge transfer resistance is 2.8 times lower than the pristine. Discharge capacity of 84% higher than pristine yields 73% higher current efficiency. It leads to improved stability and reversibility of Fe(II)/Fe(III) redox couple.